Deposit insurance structure and deposit growth dynamics: a cross-country empirical exploration - Avik Ghosh; Ankit Magotra (Cogent Economics & Finance)
This study investigates the impact of Deposit Insurance Systems (DISs) structure on deposit growth across 40 major global economies. Using panel data regression and an instrumental variable model, we find that government-administered DISs significantly reduce deposit growth, particularly in developed economies where private administration is preferred. A key contribution is the identification of DIS implementation timelines as a critical determinant of deposit dynamics. Countries introducing DISs post-2005 experience stronger deposit growth, while earlier adopters show mixed outcomes. The study also uncovers economic-size-specific heterogeneity, revealing that developed nations favor private DISs frameworks, whereas emerging economies lean towards government-backed models. This research provides novel insights into how the DIS administration influences depositor confidence and financial stability. The findings highlight the need for policymakers to tailor their DIS frameworks to national economic structures, ensuring an optimal balance between depositor protection, financial resilience, and systemic risk mitigation.